Atomically-resolved structural changes of ceramic supported nanoparticulate oxygen evolution reaction Ir catalyst. (10th September 2022) - Koderman Podboršek, Gorazd; Kamšek, Ana Rebeka; Lončar, Anja; Bele, Marjan; Suhadolnik, Luka; Jovanovič, Primož; Hodnik, Nejc
Highlights: Advanced identical location TEM was applied to TiON-supported Ir nanoparticles. Efficient control over bubble accumulation during stability test was achieved. Surface roughening revealed as the predominant degradation mechanism. Oxidation suppression of ceramic-supported Ir was confirmed. Abstract: The reduction of Ir loading and thus its efficient utilization in proton exchange membrane water electrolyzers (PEM-WE) inevitably depends on the rational design of novel nanomaterials. This, however, is not possible without the understanding of structure-stability interrelations and underlying mechanisms. When pursuing the reduction of Ir amount by its dispersion on ceramic materials, the interactions between the catalytically active sites and their support further complicate the already understood processes. In the present study, we use our unique approach, where we employ an Ir/TiON-based TEM grid and use it as a support system for the investigation of structural transformations of Ir nanoparticles. This was achieved by utilizing both the modified floating electrode (MFE) apparatus, which enables efficient bubble management during electrochemical experiments and identical-location scanning transmission electron microscopy (IL-STEM) approach. The analysis of obtained high-resolution images with in-house developed computer algorithms for image analysis reveals several processes with surface roughening being the predominant degradation mechanism. Additionally, suppressed oxidation tendency of supported Ir was directly confirmed. Abstract : Image, graphical abstract